SOSIALISASI KEJAHATAN SIBER DAN PERLINDUNGAN DATA PRIBADI UNTUK MENCEGAH PENIPUAN BERBASIS ONLINE TERHADAP MASYARAKAT - Amos Pah, Clarissa Elfira; Mola, Sebastianus Adi Santoso; Ledoh, Juan Rizky Mannuel; Pandie, Emerensye Sofia Yublina; Fanggidae, Adriana; Giri, Imanuel Raja (LPPM Universitas Flores, 2025)
During 2023, criminals carried out thousands of cyber-attack cases that harmed the community economically. Losses due to cybercrime worldwide in 2023 reached US 8 trillion and there have been more than 361 million cyber-attacks in Indonesia from January to October 2023 according to data from the National Cyber and Crypto Agency. Activities that are often reported and become the main target of cybercrime are online buying and selling which ranks 1st, followed by scamming, fictitious online investment, online work fraud, online extortion, and web phishing. Seeing the large number of victims caught in cyber-attacks, as a form of contribution to the community in the field of technology, we conducted a socialization of cyber security and privacy protection to increase public sensitivity to the dangers of cyber-attacks and prevention tips. The stages of implementation that have been carried out are visitation and licensing, observation and information gathering, making cooperation agreements, preparation of presentation materials, technical preparation, and implementation of socialization. This socialization has also been covered in the Pos Kupang electronic media and received a positive response from all participants.